THE EFFECTIVENESS OF COGNITIVE BEHAVIOR THERAPY WITH COGNITION RESTRUCTURING TECHNIQUES TO OVERCOME STUDENTS' ANXIETY IN FACING THE NATIONAL EXAM AT SMPN 1 WANASARI - Yovian Yustiko Prasetya (International Conference on Economic Business and Social Science, 2023)
This study aimed to determine whether the Cognitive Behavior Therapy with cognitive restructuring technique could lower the anxiety of student’s facing the national examination at SMPN 1 Wanasari. The type of this research was pre-experiment research by using quantitative approach. The design in this study used one group pre-test post-test only. This experimental study referred to the high level anxiety of learners in facing national examination at SMPN 1 Wanasari from year to year. Anxiety learners to the national exam was due to misinterpretation by learners of the national examination moment. The research subjects were 5 students who entered the category of very anxious based on pre-test score. Data collection technique used was questionnaire. The statistical analysis technique used was Wilcoxon non-parametric statistics. The results showed that Wilcoxon's "test statistic" output table was known Asymp.Sig. (2tailed) was 0.042. Because of the value of Asymp.Sig. (2tailed) was smaller than 0.05, it was concluded that H0 was rejected and Ha was accepted or in other words that the use of Cognitive Behavior Counseling with cognitive restructuring technique was effective to overcome the anxiety of learners in facing the national examination in SMPN 1 Wanasari